Vous êtes sur la page 1sur 5

ABSOLUTE VALUE

a 2 .b3

e.g.(3) If a0b, then simplify

a 3 .b 4

(answer: 6 b )

1. Definition of Absolute Value


e.g.(2) Find x in the equation
Definition: Let x be a real number.Absolute value of x
which is denoted by x is defined as

answer: x {8; 4}
e.g.(2) If x 3 ;then simplify

x, if x 0
x =
-x, if x0

( x + 2) 4 = 6

x2 4 x + 3
x 1

x2 9
x+3

(answer: -2x+6 )
e.g.(2) If 3 x 5 ,then simplify

e.g.(1) Evaluate 7 3 2 . (answer : 2)

x 2 + 7 x + 4 + x 2 10 x + 25

( answer : x + 3 )

e.g.(2) If a<0<b, then a a b = ? (answer : -b)

e.g.(2) If x<0<y<z, then find

yz + yx
x+ z

Geometric Meaning Of Absolute Value


. (answer : 1)

Let x 0 , then x means the distance of the point x from


the point 0 on real number line.

Some Properties Of Absolute Value


Graph Of Absolute Value Functon

1) x 0 for any x.
2) x = x ; x y = y x for any x and y.

Properties
1) D(f) = ( ; )

x = a
3) If x = a, then
where a 0.
x = a
4) x. y = x . y for any x and y.
5)

2) E(f)= [ 0 ; )
3) x-intercept : x = 0
4) x decreases when x ( - ; 0]
5) x increases when x [ 0 ; )
6) Absolute value function is even,so its graph is

x
x
=
for any x and y 0 .
y
y

6) x n = x

symmetric with respect to y- axis.

x = y
7) If x = y , then
x = y

2. Solving Absolute Value Equations


Equations in the Form f ( x ) = c , c

8) If x a, then a x a where a 0

x a
9) If x a, then
where a 0
x a

f ( x) = c
f ( x ) = c

a) If c 0 ; then

a x b
where a 0, b 0
10) If a x b, then
a x b

b) If c = 0 ; then f ( x ) = 0
c) If c 0 ; then x

11)

x,if n is odd
xn =
where n 2
x ,if n is even

e.g.(1) Solve 2 x 3 = 5 (answer: x {1; 4} )


e.g.(1) Solve x + 2 = 1

12) x + y x + y for any x and y.

e.g (2) Solve


e.g.(1) Find x if 5 x 7 = 3 . (answer: x )
e.g.(2) Evaluate

(7) 2 + 4 ( 5) 4 + 3 (2)3

(answer:10)

(answer: x )

x 2 8 = 3 (answer: x {9; 3; 7;13} )

e.g (2) Solve x 2 + 2 x 3 = 5 (answer: x {1; 4} )

Equations in the Form f ( x ) = f ( x )

e.g.(2) Solve x 2 6 x + 8 = 0

f ( x); f ( x) 0
f ( x) =
f ( x); f ( x) 0

x 6 x +8 = 0
2

e.g.(1) Solve x 8 = x 8 (answer: x 8 )


(answer: x 0 )

e.g.(1) Solve x + x = 0

Equations Solved by Changing Variable

e.g.(1) Solve x + x 2 = 2 (answer: x 2 )

Let x = t , t 0 ;
then we will have t 2 6t + 8 = 0
and (t 4) (t 2) = 0

Equations in the Form f ( x ) = g ( x )

x =4
t1 = 4
t = 2 so
2
x = 2

f ( x) = g ( x )
f ( x) = g ( x )

4
e.g.(1) Solve 2 x 3 = x + 7 (answer: x ;10 )
3
e.g.(1) Solve x 2 1 = x + 5

(answer: x {2;3} )

Equations in the Form f ( x ) = g ( x )

If

f ( x) 0,

f ( x) = g ( x)
f ( x ) = g ( x ) ; then
f ( x) 0,

f ( x) = g ( x)

e.g.(1) Solve 2 x 3 = x 2

2x-3 0,

2x-3 = x 2
2x-3 0,

(2 x 3) = x 2

x
x

Answer: x {4; 2; 2; 4}
e.g.(2) Solve (2 x 3) 2 x 6 = 0

1 1

answer: x 3; ; ;3
4 4

e.g.(3) Solve x 2 + 2 x 4 x + 1 4 = 0

answer: x {6; 4}
e.g.(3) Solve 4 x 2 12 x + 9 3 2 x 3 4 = 0

1 7
answer: x ;
2 2
3
,
2
x =1
x

Equations in the Form f ( x ) + g ( x ) = f ( x ) g ( x )


e.g.(2) Solve x 1 + x 3 = 2 x 4

3
,
2
5
x=
3
x

(x 1) + ( x 3) = 2 x 4 so;

x 1 0,

x 3 0

answer: x

e.g.(1) Solve x + 2 x = 1 (answer: x =

e.g.(2)Solve 2 x 2 1 = x 2 2 x + 3

x 1,

x 3

x3

answer: x [3; )
1
)
3

e.g.(2) Solve x. x 3 = 4 (answer: x = 4 )

(answer: x1,2 = 1 5 )

x1 = 4
x = +4
2
x3 = 2

x4 = +2

e.g.(2) Solve x + 5 + 3 x = 8

answer: x [ -5;3]
e.g.(2) Solve 2 x + 5 + 2 x 1 = 6

5 1
answer: x - ;
2 2

e.g.(3) Solve x 2 3 x 7 3

e.g.(2) Solve 2 x 4 + x 1 = 3 x

answer: x [1; 2]

( answer: x ( ; 2) or x ( 1; 4) or x (5; ) )

e.g.(3) Solve

e.g.(3) Solve x 2 x + 3 = x 1

2
3
answer: x (; 1) or x (1;0) or x ;1 or x 1;
3
2

answer: x = 0

3. Absolute Value Inequalities


f ( x) c , c

Inequalities in the Form

x 2 3x + 1
1
x2 1

a) If c 0 , then c f ( x ) c

e.g.(3) Solve

3x
1
x 4
2

answer: x ( ; 4 ] or x [ 1;1] or x [ 4; )
Inequalities in the Form f ( x ) g ( x )

b) If c 0 , then x
(Similarly, if f ( x ) c, then c f ( x ) c ;where c 0)

e.g.(1) Solve 3 x 1 x + 3 (answer: 0 x 3 )

e.g.(1) Solve x 1 2

(answer: x ( 1;3) )

1
e.g.(1) Solve 2 x 3 4 5 x answer: x ;
3

e.g.(1) Solve 2 x 1 3

(answer: x [ 1; 2 ] )

e.g.(2) Solve x

e.g.(3) Solve x 2 3 x 4 6

1
x

answer: x ( ; 0) or x (1; )

answer: x (2;1) or x (2;5)

e.g.(3) Solve x 2 1 2 x + 2 (answer: x ( 1;3) )

e.g.(3) Solve x 2 5 4

Inequalities in the Form f ( x) g ( x )

answer: x ( 3; 1) or x (1;3)

We can take the squares of both sides

e.g.(3) Solve

x 7 + x2 + 3
x +3 7
2

Inequalities in the Form

(answer: x ( 2; 2) )

f ( x) c , c

f 2 g2
f 2 g2 0
( f g )( f + g ) 0

or

b) If c 0, then x

2
answer: x (; or x [ 4; )
5
e.g.(2) Solve

e.g.(1) Solve 3 x 1 5

4
(answer: x ( ; or x 2; ) )
3
e.g.(2) Solve

2x + 3
2
1
1 ( answer: x ;5 or x )
3x 2
3
5

answer: x (3; )

e.g.(1) Solve 1 3 x 2 x + 3

e.g.(1) Solve 5 x 7 3

answer: x ; or x (2; )
5

f 2 g2 0

or ( f g )( f + g ) 0

e.g.(1) Solve x 4 x 2

f ( x ) c,
a) If c 0, then
f ( x ) c

f 2 g2

or

2
3

x2
2x 1

8
answer: x (; 4) or x ; 2 or x (2; )
7
e.g.(2) Solve x 1 x 2 x 2 3 x + 4

answer: x ;
2

Inequlities Solved by Changing Variable


e.g.(1) Solve

2
x 2
x +1

answer: x ( ; 8) or x (2; )

2
or x ;

3
1
3

(answer: [ 0;1] )

e.g.(2) Solve x 3 x + 5 + x 0

e.g.(1) Solve 6 x 2 x 2 0

e.g.(1) Solve x 2 + 2 x + 1

answer: x ( ;1) or x (3; )

e.g.(2) Solve x + x 1 1

answer: x ( 1; 0) or x (0;1)

answer: x ;
3

x 1
x 3

(answer: x )

e.g.(1) Solve x x 0

e.g.(3) Solve x 3 + x 2 1 + x 14

answer: x ( 2 3 ; 19 1)
Exercises

ex: (2) Solve ( x 1 3)( x 3) 0

answer: x ( 1;1) \ {0}

e.g.(2) Solve

3 x +2
x 1

answer: x ( ; 2) or x (3; 4)

1 1
(answer: x ; )
6 6

e.g.(2) Solve ( x 1) 2 2

answer: x ( ; 1 2) or x (1 + 2 ; )

e.g.(2) Solve

x2 4 x + 4 x 2
+
12 0
x2 6 x + 9 x 3

ex: (3) Solve x 2 9 ( x 2 7 x + 10) 0

answer: x ( 5; 2) \ {3} or x (2;5) \ {3}


ex: (2) Solve

2 x
3
x

answer : x 1; \ {0}
2

ex: (2) Solve x x 1 2

answer : x ( ; 2)

ex: (2) Solve x x + 5 + 6 0

11

7
answer: x ; or x ;
4

2
Inequalities in the Form f ( x ) + g ( x ) c, c > 0
e.g.(2) Solve x 1 + x 3 2

x 1,

2 x + 2 0
1 x 3,

0 0

x 3,

2 x 6 0

ex: (2) Solve

ex: (3) Solve

x2 6 5

x x 2
x2 5x + 6
x2 1

answer : x ( ; 6)

7
answer : x ( ; 1) or x 1;
5
ex: (3) Solve

x 1,

x 1
{no solutions

x 3,

x 3

x+3 + x

1
x+2
answer : x ( 5; 2) or x ( 1; )

ex: (2) Solve

Critical points are x = 1 and x = 3.So


a ) If x 1, then we will have
( x 1) ( x 3) 2
b) If 1 x 3, then we will have
( x 1) ( x 3) 2
c) If x 3, then we will have
( x 1) + ( x 3) 2

answer : x ( 6; )

17 3x 2
x 2 + 5 x 14

19
answer : x ( ; 7 ) or x ( 2;5 ) or x ;
3

ex: (3) Solve

23 x
1+ x

3 1
1 3
answer : x ; or x ;
2 4
4 2
ex: (3) Solve 2 x 3 x 2

answer : x ;
3

ex: (3) Solve

5
or x ;

x3 x 2 + 2 x 2
0
x +1 3

answer : ( ; 2) \ {4; 1}

ex: (3) Solve

2 x x
x 3 1

answer : x ( , 2 ) or x ( 4; )